Induction Heating of Very Thin Metal Plates Modelled by Electric Vector Potential - Dolezel, Ivo; Ulrych, Bohus (Communications - Scientific letters of the University of Zilina, 2011)
A novel way of modelling of induction heating of very thin nonferromagnetic plates exposed by periodically varying magnetic flux is presented. The currents induced in the plate are described by means of the T-electric vector potential. The mathematical model is solved numerically, by a code developed and written by the authors. The methodology is illustrated with an example whose results are discussed.